THE EFFECT OF ART THERAPY ON IMPROVING THE COGNITIVE FUNCTION OF ELDERLY IN NURSING HOMES IN SEMARANG - Kareena Kumar; Yosef Purwoko; Soesmeyka Savitri; Dwi Ngestiningsih (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: Art therapy is a creative process that utilizes art and psychology aspect in an effort to learn something new about oneself. Art therapy can help individuals to express their feeling as a mental stimulation which in long term can increase the regeneration of new neurons which will later have an effect on cognitive function improvements. Improving cognitive function in elderly can increase their ability to do their daily activities independently. Objective: To assess the effect of art therapy on improving elderly’s cognitive function in nursing homes in Semarang. Methods: Quasy experimental research using pre and post-test design with control group methods. Subjects were 32 elderlies who lived in Wisma Lanjut Usia Harapan Asri, Panti Wredha Rindang Asih II Bongsari, or Panti Wreda Pengayoman Semarang. Subjects were >60 years old, had a cognitive function score ≥ 22 using MoCA-Ina instrument, and were not taking any sedative drugs. Sample selection was picked using purposive sampling method and grouped into 2 groups. The art therapy intervention group (n=16) was instructed to follow the all four interventions of art therapy, while the control group (n=16) was instructed to not doing any art drawing activities. Cognitive function scores were measured using MoCA-Ina. The data then analysed using Wilcoxon and Mann-Whitney. Results: Significant increase (p < 0.05) in the MoCA-INA scores of intervention group from 25,44 ± 2,128 to 26,38 ± 2,094. There was significant difference of MoCA-INA scores between intervention group which was 26,38 ± 2,094 and control group which was 24,13 ± 1,5. Conclusion: Art therapy is effective in improving cognitive function of elderly in nursing home in Semarang.